Transgenic tobacco plants having a higher level of methionine are more sensitive to oxidative stress. Issue 3 (3rd May 2017) - Hacham, Yael; Matityahu, Ifat; Amir, Rachel
Abstract : Methionine is an essential amino acid the low level of which limits the nutritional quality of plants. We formerly produced transgenic tobacco ( Nicotiana tabacum ) plants overexpressing CYSTATHIONE γ‐SYNTHASE (CGS) (FA plants), methionine's main regulatory enzyme. These plants accumulate significantly higher levels of methionine compared with wild‐type (WT) plants. The aim of this study was to gain more knowledge about the effect of higher methionine content on the metabolic profile of vegetative tissue and on the morphological and physiological phenotypes. FA plants exhibit slightly reduced growth, and metabolic profiling analysis shows that they have higher contents of stress‐related metabolites. Despite this, FA plants were more sensitive to short‐ and long‐term oxidative stresses. In addition, compared with WT plants and transgenic plants expressing an empty vector, the primary metabolic profile of FA was altered less during oxidative stress. Based on morphological and metabolic phenotypes, we strongly proposed that FA plants having higher levels of methionine suffer from stress under non‐stress conditions. This might be one of the reasons for their lesser ability to cope with oxidative stress when it appeared. The observation that their metabolic profiling is much less responsive to stress compared with control plants indicates that the delta changes in metabolite contents between non‐stress and stress conditions is important for enabling the plants to cope with stress conditions.